2023
DOI: 10.1002/app.54064
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible poly(glycerol sebacate) base segmented co‐polymer with interesting chemical structure and tunable mechanical properties: In vitro and in vivo study

Abstract: In this study, different polycaprolactone (PCL) soft blocks were incorporated into poly(glycerol sebacate) (PGS) structure to prepare a series of PGS‐based elastomers with a wide range of chemical compositions, mechanical properties, and modulated degradation behavior. The PGS and PGS‐co‐PCL elastomers were prepared under a thermal curing process in the absence of any catalysts. Here, in addition to the effect of different lengths of PCL block, the effect of thermal curing time on the mechanical properties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
(120 reference statements)
0
2
0
Order By: Relevance
“…However, these modifications lead to reduced biocompatibility and affect the physical and mechanical properties. 18,25,31 In other words, blending gives controllability of degradation by maintaining other properties, which means that by blending bioelastomers, the required properties can be preserved, and the degradation rate can be adjusted for long-term and short-term tissue engineering purposes.…”
Section: In Vitro Degradation Characterizementioning
confidence: 99%
See 1 more Smart Citation
“…However, these modifications lead to reduced biocompatibility and affect the physical and mechanical properties. 18,25,31 In other words, blending gives controllability of degradation by maintaining other properties, which means that by blending bioelastomers, the required properties can be preserved, and the degradation rate can be adjusted for long-term and short-term tissue engineering purposes.…”
Section: In Vitro Degradation Characterizementioning
confidence: 99%
“…24,[27][28][29][30] Through the blending of poly (glycerol sebacate) with polycaprolactone, it has been demonstrated that it is possible to maintain biocompatibility at a level comparable to pure poly (glycerol sebacate) while also achieving a wide range of mechanical properties. 31 Piatek-Hnat et al studied the effects of radiation modification of sugar alcohol-based bioelastomers and reported that these polymers are well-suited for radiation modification. The study's results revealed that radiation could effectively modify the mechanical properties and cross-link density of the bioelastomers, providing an advantage in sterilization for medical applications.…”
Section: Introductionmentioning
confidence: 99%